Implementasi Standar Pelayanan Minimal Bus Antarkota dan Antarprovinsi di Terminal Purabaya Tahun 2021 - Miftahus Surur; Helmy Boemiya (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
Indonesia based on its geographical location consists of 13,667 islands, this condition encourages and is the reason for the use of adequate means of transportation. East Java province there are types of public transportation. Law No. 22 of 2009 concerning road traffic and transportation in article 141 regulates minimum service standards which are further regulated in Permenhub No. 98 of 2013 and its amendments in Permenhub 29 of 2015. Service standards include security, safety, comfort, affordability, equality and regularity in running the AKAP bus. However, there are still problems in running public transportation that trigger the cause of road accidents. On the basis of these problems raises two problem formulations. What is the form of implementation of minimum service standards for transportation of people with public motorized vehicles on the route at the Purabaya terminal, and how effective is the implementation of minimum service standards for inter-city and inter-provincial buses at the Purabaya terminal.The type of research used is empirical legal research, research focuses on legal issues that are the reason for this research, the problems discussed in this research are vague of norm, and legal sociology approach and conceptually sourced from primary data and secondary data which are then concluded in the process of data analysis.The results of this study indicate that the implementation of minimum service standards is implemented at the Purabaya terminal with several other components, namely route permits, motor vehicle feasibility tests (KIR) and KPS (supervision cards). As well as the effectiveness in its application in terms of several approaches, including the target approach, source approach, and process approach, there are still several components that are not yet effective.